Proconvulsant effect of aminophylline on cortical epileptic afterdischarges varies during ontogeny - Bernásková, K; Mares, P (Epilepsy research, 2000)
Effect of aminophylline on epileptic afterdischarges (ADs) induced repeatedly by rhythmic electrical stimulation of sensorimotor cortical area was studied in rat pups 12, 18 and 25 days old. The proconvulsant effect of aminophylline (50 and/or 100 mg/kg i.p.) was more expressed in 12- and 18-day-old rats than in the oldest group. In 12-day-old rat pups there was an enormous increase of transition of the spike-and-wave type of ADs into the second, limbic type, a situation observed only exceptionally under control conditions. A prolongation of ADs was related to this transition (limbic ADs are always longer than spike-and-wave ones). Eighteen-day-old rats exhibit this transition less frequently but a marked prolongation of spike-and-wave ADs was recorded in a part of these animals forming a pattern of status lasting some tens of minutes. Aminophylline led only to a transient prolongation of spike-and-wave ADs in the oldest group. The transition into the limbic type of ADs was seen in this age group only exceptionally what is in contrast to age-matched controls in which this transition is common. The effect of aminophylline on cortical ADs which is most marked in the youngest group changes qualitatively during postnatal development.
Keywords: Animals; elektrická stimulace; Electric Stimulation; Movement; Epilepsy; Convulsants; Female; Rats, Wistar; Electrodes, Implanted; pohyb; aminofylin; ženské pohlaví; somatosenzorické korové centrum; Motor Cortex; chování zvířat; Bronchodilator Agents; těhotenství; Somatosensory Cortex; epilepsie; konvulziva; motorické korové centrum; implantované elektrody; krysa rodu Rattus; Behavior, Animal; mozková kůra; Aminophylline; Cerebral Cortex; zvířata; Pregnancy; elektroencefalografie; bronchodilatancia; Rats; Electroencephalography; potkani Wistar